Colecciones microbianas : importancia, establecimiento y regulación (2013)
ABSTRACT: Microbial collections are ex situ repositories of microorganisms that present new features or that show important potential for health or industry. They enable preservation, maintenance and availability of microorganisms. Increasing demand for microbial collections, the complexity of their tasks and the importance of service quality requires knowledge of guidelines for these collections. This review deals with the importance of microbial collections, the processes required for its establishment and leading organizations for its regulation.